PENGARUH PROFITABILITAS DAN PERTUMBUHAN AKTIVA TERHADAP CORPORATE GOVERNANCE DAN STRUKTUR MODAL - Darmayanti, Ni Putu Mirah; Wiagustini, Luh Putu; Rahyuda, Henny (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.12.TAHUN 2016, 2016)
This study purposed to examine (1) the effect of)profitability on the capital structure, (2) asset growth on the capital structure, (3) profitability on corporate governance, (4) asset growth on corporate governance, and (5) corporate governance on the capital structure. The research´s population was a company registered as a participant in the Corporate Governance Perception Index (CGPI) and the Indonesia Stock Exchange period 2010-2014. The analysis technique used is path analysis using SPSS. The results showed that the profitability has a negative significant effect on the capital structure, assets growth and corporate governance has significant effect to capital structure, profitability has a significant and negative related to corporate governance, and asset growth has not significant effect to corporate governance.
Keywords: Profitability, Growth Assets, Corporate Governance and Capital Structure